Transforming Intercultural Perspectives: Reflecting On-line - Linda Ziegahn (Adult Education Research Conference, 1998)
The purpose of this exploratory study was to understand how students in an online course showed evidence of reflection and transformative thinking around issues of social justice and intercultural communication. Email transcripts from six students were analyzed for evidence of reflection on underlying assumptions regarding course content. Results suggest that the range of kinds of reflection on premise described by Mezirow (1991) are all present, that each student has a "refective style", and that transformation around issues of race was compromised by frustration with the concept of white identity.